Microbes as Teachers: Rethinking Knowledge in the Anthropocene - Rachel Armstrong (Microbial Biotechnology)
ABSTRACT This opinion piece proposes that the environmental crises of our time arise from a failure to recognise the vital role of microbes in sustaining life on Earth, where ecosystems have been shaped for billions of years by microbial processes, including oxygen production, nutrient cycling and climate regulation. Yet the idea that microbes can ‘teach’ us how to navigate complexity, adapt across scales, and sustain planetary systems is still marginalised in science, policy, and education. A paradigm shift is proposed: microbes must be reframed as active collaborators in solving global challenges. This perspective is grounded in microbial ecology, Indigenous knowledge, and ethical philosophy, advocating for ‘learning’ through and with microbial life. To institutionalise this transition, policy and educational reforms are urged, centring microbial literacy as a foundation for ecological understanding. By integrating microbial agency into human knowledge systems, societal actions could be realigned with the biochemical and evolutionary logics that have sustained life for millennia. Ultimately, a deeper engagement with microbial knowledge is called for—one that informs a more sustainable future.